Effect of Government Debt on the Non-Oil Trade Balance in Iraq for Period (2004-2020) - Malik Abdul Raheem Mohammed; Isam Abdul Khudhur Saud; Mustafa Kamil Rasheed (Genius Journals, 2022)
Increase in the prices of crude oil and the quantities exported from it, achieved financial surpluses that prompted the Iraqi government to adopt government debt, as a means to increase government consumer spending and the expansion of the government sector. However, the expansionary fiscal policy did not succeed in activating the production sectors, so most of the local production branches continued to suffer from permanent disruption and imbalance. research aims to measure the impact of internal and external government debt on the non-oil trade balance, to know the economic loss facing the Iraqi economy. problem of the research is that the continuation of government debt without the development of domestic production makes the cost of debt exorbitant for the economy and future generations. research concluded that there is a strong relationship between the internal and external government debt in the non-oil trade balance, which warns of the risk of not being able to pay in the future. research recommended the importance of following up on production activities and restricting imports to serve sustainable development plans
Keywords: Internal government debt; external government debt; balance; GDP